THE HOT “COLD WAR”: THE USSR IN SOUTHERN AFRICA - Visser, Deon (Scientia Militaria - South African Journal of Military Studies, 2011)
Vladimir Shubin is the Deputy Director of the Institute for African Studies in the Russian Academy of Sciences and a former officer in the Soviet armed forces, and subsequently, a member (eventually secretary) of the Soviet Afro-Asian Solidarity Committee and desk officer (eventually head) of the African Section of the Communist Party of the USSR. In the latter two capacities he became intensely involved in supporting Southern African liberation movements on behalf of the USSR. In The Hot “Cold War”: The USSR in Southern Africa Shubin aims to ‘set the record straight’ with regard to Moscow’s involvement in Southern Africa during the Cold War, especially the role of the Soviet military, which he believes ‘is covered inadequately or even distorted’ (p. xv). His work is divided into five parts dealing in succession with the liberation struggles in Angola, Mozambique, Zimbabwe, Namibia and South Africa during the period 1960 to 1990.